2023
DOI: 10.1177/23247096221150631
|View full text |Cite
|
Sign up to set email alerts
|

A Pair of Siblings With Wolfram Syndrome: A Review of the Literature and Treatment Options

Abstract: Wolfram syndrome (WS) is a rare genetic disorder typically characterized by juvenile onset diabetes mellitus, optic atrophy, hearing loss, diabetes insipidus, and neurodegeneration. There would be a high index of clinical suspicion for WS when clinical manifestations of type 1 diabetes and optic atrophy present together. Genetic analysis is often required to confirm the diagnosis. We describe a pair of Chinese siblings diagnosed with WS at ages 20 and 24 years, respectively. DNA sequencing of the WFS1 gene whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Salzano et al reported heart diseases in 14.3% of 14 patients, including VSDs, and secundum atrial septal defects (ASDs) with concomitant valvulopathy [ 9 ]. ASDs were also described in one of a pair of Chinese siblings [ 10 ]. In 16.1% of 31 Lebanese patients, valvular heart disease, particularly pulmonary stenosis, was described [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salzano et al reported heart diseases in 14.3% of 14 patients, including VSDs, and secundum atrial septal defects (ASDs) with concomitant valvulopathy [ 9 ]. ASDs were also described in one of a pair of Chinese siblings [ 10 ]. In 16.1% of 31 Lebanese patients, valvular heart disease, particularly pulmonary stenosis, was described [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed a decrease in insulin requirement, stabilization of neuroophthalmological and neurophysiological disease parameters, and no onset of new WFS1-SD-related symptoms at the latest follow-up (18). Accordingly, a very recent case report described the treatment of a WFS1-SD patient with 0.6 mg per day liraglutide in association with the chemical chaperone tauroursodeoxycholic acid (TUDCA) to mitigate ER stress, reduce insulin requirements, and improve glycemic control (82).…”
Section: Preclinical and Clinical Use Of Glp-1ras In Wfs1-sdmentioning
confidence: 99%